2012
DOI: 10.1097/nmc.0b013e31823851ee
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Management Information Needs of Postpartum Women

Abstract: Postpartum hospital nurses are in a unique position to provide high-quality information with strategies for managing postpartum loss of gestational weight. Provision of high-quality online or print information can provide the foundation for successful weight-management support for prevention of gestational weight retention and long-term maintenance of a healthy weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
(17 reference statements)
0
19
0
Order By: Relevance
“…This systematic review presents a summary of lifestyle interventions aimed at decreasing maternal PPWR, showing that while this outcome is possible, many uncertainties remain as to the most effective approach in supporting women to lose weight during this life stage. The unique period following childbirth has been described as an ideal stage in which to engage with women in promoting healthy weight attainment and is an important time for altering long‐term obesity risk for mothers experiencing PPWR. However, studies targeting healthy maternal weight during the postpartum have been varied in their intervention setting, delivery method and intervention components, recruitment time and assessment of anthropometric outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review presents a summary of lifestyle interventions aimed at decreasing maternal PPWR, showing that while this outcome is possible, many uncertainties remain as to the most effective approach in supporting women to lose weight during this life stage. The unique period following childbirth has been described as an ideal stage in which to engage with women in promoting healthy weight attainment and is an important time for altering long‐term obesity risk for mothers experiencing PPWR. However, studies targeting healthy maternal weight during the postpartum have been varied in their intervention setting, delivery method and intervention components, recruitment time and assessment of anthropometric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the majority (89%) of women reported receiving no weight loss nor physical activity advice (77%) during the postpartum period . In a separate study of 179 women, at 4 months postpartum, half (53%) of normal weight women, 79% of overweight women and 81% of obese women reported plans to seek weight loss information, despite 85% of the women overall having received no weight loss information from healthcare providers . Therefore, the postpartum period might be considered a missed opportunity for clinically guided weight management.…”
Section: Introductionmentioning
confidence: 98%
“…The increased participation also resulted in more than twice as much weight loss in the telephone‐delivered program. We know postpartum women are ready and motivated to lose weight . However, the competing postpartum demands such as time pressure, tiredness or fatigue, newborn childcare, other family commitments, change in priorities, and the lack of social support can reduce a mother's ability to engage in lifestyle behavior change .…”
Section: Discussionmentioning
confidence: 94%
“…We know postpartum women are ready and motivated to lose weight. [60][61][62][63] However, the competing postpartum demands such as time pressure, tiredness or fatigue, newborn childcare, other family commitments, change in priorities, and the lack of social support can reduce a mother's ability to engage in lifestyle behavior change. 55,60,62 Wide ranges of attrition rates in existing RCTs (0%-42%) suggest considerable barriers exist for postpartum mothers, but no RCTs in the current review focused on addressing these barriers to participation.…”
Section: Discussionmentioning
confidence: 99%
“…E-Health-the delivery of health care services and information via internet and related technologies-may fill information needs mothers confront during this transition (Eysenbach, 2001). Those needs include postpartum depression, weight retention, parenting, and other concerns (Kanotra et al, 2007;Ohlendorf, Weiss, & Ryan, 2012). These and other topics are gaps in health care of postpartum women (Sword & Watt, 2005;Walker, Murphey, & Xie, 2016).…”
mentioning
confidence: 99%